Integrating industry 4.0 into higher education: a case study of a drone course for multidisciplinary learning course - Hussain, Afifuddin Husairi; Ummihusna, Annisa; Eni, Sabariah; Wan Mohamad, Wan Nurashiqin; Che Musa, Normazidah (Human Resource Management Academic Research Society, 2024)
This study investigates the integration of Industry 4.0 (IR4.0) technologies into higher education, focusing on a co-curricular drone course designed to prepare students for future career landscapes. The research aims to assess student engagement, the effectiveness of hands-on learning approaches, and the alignment of the course with the needs of IR4.0. Utilizing a case study approach, we collected data from a cohort of students across various disciplines at a higher education institution (HEI). The course incorporated a kinesthetic learning model, where students tackled real-world industry problems using drones, guided by experts from the drone sector. Feedback was gathered through structured online questionnaire to evaluate the course's impact and areas for improvement. The study revealed strong student enthusiasm for drone technology and IR4.0 applications, driven by curiosity, career prospects, and personal interests. Students advocated for more practical, hands-on activities and increased interaction with industry experts. The findings underscore the need for HEIs to develop flexible, future-oriented curricula that can adapt to diverse student profiles and rapidly evolving technological landscapes. Challenges identified include course design, pedagogical strategies, and the need for adequate teaching facilities and evaluation methods. This research highlights the importance of creating educational frameworks that are agile and responsive to the demands of IR4.0. It suggests a synergistic approach involving government, industry, and academia to foster high-quality talent capable of thriving in the digital era. The study also points to the necessity of addressing diversity and inclusion to bridge gender and rural-urban gaps in technology education. This work provides valuable insights into the practical integration of IR4.0 technologies in higher education. It offers a baseline for other HEIs to design and enhance their IR4.0 curricula and suggests areas for future research to optimize educational strategies in preparing students for a dynamic, technology-driven world.